"BOYS DO NOT DRESS LIKE GIRLS": DESTABILIZING STANDARDIZATIONS OF BODIES, GENDER AND SEXUALITY WITH THE SHORT FILM VESTIDO NUEVO - Sousa, Marcos Lopes de; Ferrari, Anderson (Cadernos de Educação Tecnologia e Sociedade, 2016)
The Spanish short film Vestido Nuevo tells the story of the boy Mario who goes to school on Carnival’s celebration day with a pink dress and painted nails causing the estrangement of the school community. Having this cultural artifact to trigger discussions on gender and sexual diversity, this article discusses three scenes that the participants of the Institutional Grant Program for Teaching Initiation (PIBID) captured related to early childhood education a Federal University in Minas Gerais, during a training meeting in which they worked with the short film. The methodological theoretical perspective that organizes our analysis is post structuralism, focusing on the discourse emergence conditions of and how they invite us to think about our subjectivity modes. The dialogues about the scenes contributed to questioning the participants’ opinions on the issues of bodies, genders and sexualities, among which: the tensions involving the families of students who transgress the norms; the multiple reactions from classmates of those who are perceived as gender and sexual dissidents and the possible attitudes from the educators when faced with situations in school with children who do not conform to the normative gender.